Radiosensitization by Marine Sponge Agelas sp. Extracts in Hepatocellular Carcinoma Cells with Autophagy Induction - Changhoon Choi (Nature Portfolio, 2018)
Abstract Although radiation therapy is an effective treatment modality in many cancers, there is an urgent need to develop therapeutic drugs capable of overcoming radioresistance or minimizing normal tissue toxicity. A wide variety of marine-derived bioactive compounds have been screened for anti-cancer drug discovery, but little is known regarding radiation therapy applications. In this study, six different extracts of marine sponges collected from the Micronesian sea were screened for anti-cancer and radiosensitizing activity. Two extracts derived from Agelas sponges collected off the coast of Kosrae and Chuuk, the Federated States of Micronesia significantly decreased clonogenic survival of hepatocellular carcinoma (HCC) cells after exposure to ionizing radiation (IR). The Agelas extracts augmented IR-induced apoptosis and accumulation of reactive oxygen species (ROS). Endoplasmic reticulum (ER) stress was increased via unfolded protein response stimulation, which induced autophagy. N-acetylcysteine, a ROS scavenger, diminished ER stress and autophagy induction effects. This result indicated that Agelas extracts may sensitize HCC cells to IR via ROS overproduction in vitro. Our findings suggest that the Agelas sp. may have potential utility in radiosensitizer development.